Antimicrobial and plant growth-promoting activity of Bacillus subtilis isolated from mangrove soil. - Shinde, P. A.; Karnik, P. N.; Karshinkar, J. U.; Coutinho, R. A.; Rodrigues, P. J.; Chavan, S.; Chakraborty, P. (International Journal of Agricultural Technology, 2025)
Bacillus subtilis strain was isolated from mangrove soil and evaluated for its biocontrol and plant growth-promoting potential. The strain exhibited key traits including indole-3-acetic acid (IAA) production, biofilm formation, and tolerance to high salinity (up to 10% NaCl). It showed broad-spectrum antimicrobial activity, inhibiting the growth of both fungal and bacterial pathogens. Antifungal activity was demonstrated using well-diffusion and dual-overlay assays, effectively suppressing Aspergillus niger, Rhizopus arrhizus, and Mucor mucedo. Antibacterial effects were observed against Escherichia coli, Bacillus albus, and Xanthomonas sp. The cell-free supernatant of the isolate significantly inhibited fungal spore germination, as confirmed by turbidity assays. LC-MS analysis of the supernatant revealed the presence of antimicrobial compounds, including palmitic acid derivatives, fatty acid amides, and pyridine-based molecules. Bio-priming wheat seeds with this Bacillus sp. led to enhanced seed germination and increased shoot and root lengths, especially under saline soil conditions. These findings highlight the potential of this mangrove-derived B. subtilis strain as a promising bioinoculant for sustainable agriculture, particularly in salt-affected environments.